PERAN GURU BIMBINGAN KONSELING DALAM PENYELESAIAN DEGRADASI MORAL SISWA SMPN 23 PEKANBARU - Az-zahra Ramadhani; Khairun Nisa; Yova Sofiana; Siera Andini; Apriza Nur; Faiz Rivaldi Zulfa; Hayati Sakinah; Hambali; Rizky Dinda Sarmita Harahap (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Moral decline or what is commonly called moral degradation in junior high school students has become a serious challenge in the world of education in Indonesia. With education, people can gain knowledge and skills and understand moral and ethical values in everyday life. However, in reality, in the current era, many students are still involved in cases of moral degradation. Various efforts have been made by guidance and counseling teachers to prevent and overcome the moral degradation of students at SMP Negeri 23 Pekanbaru. This study aims to analyze and describe the role of teachers in overcoming the moral degradation of students at SMP Negeri 23 Pekanbaru. This study uses a descriptive qualitative approach. Data collection techniques used by researchers are interviews and documentation. The information we obtained from guidance and counseling teachers and 6 students from grades VII, VIII, XI. The results of the study made in iterkat guidance and counseling teachers’ efforts in overcoming moral degradation at SMP Negeri 23 Pekanbaru, teachers have made efforts, including: 1) creating a weekly education program of manners and morals. 2) implementing the 5S habit (greeting, greeting, smiling, polite, courteous). 3) not allowing students to bring cell phones to school. 4) providing consultation to students experiencing moral degradation